Is cork oak (Quercus suber L.) woodland loss driven by eucalyptus plantation? A case-study in southwestern Portugal - Costa, a; Madeira, M.; Santos Lima, J.; Costa A, Madeira M.; J, Santos Lima (iForest - Biogeosciences and Forestry, 2014)
Mediterranean landscapes with open cork oak (Quercus suber L.) woodlands have recently experienced drastic changes in southwestern Portugal. Changes in agricultural activities, the traditional driver of the economy in this region, led to new land uses such as long-term set aside (shrublands) and eucalyptus plantations. A study was conducted on the oak woodland landscape dynamics over a 50-year period (from 1958 to 2007) in order to assess the effect of different biophysical conditions on landscape spatial changes, and to identify the resilience of lanscape composition to different disturbances (e.g., socio-economic changes and wildfires). Land use changes over two consecutive periods (1958-1995 and 1995-2007) were inferred by spatial analysis of land cover data (aerial photographs) and related to landscape physical attributes (slope and soil type). A transition matrix of four vegetation land-cover classes was obtained, allowing the assessment of the landscape composition changes bewteen the two above periods. Results showed that lansdcape in 1958 was largely occupied by open farmland, with large patches of open oak woodlands on steep slopes surrounding watercourses. Open farmland and shrubland drastically declined from 1958 to 1995, while eucalyptus plantation exhibited a dramatic expansion. Although large areas of cork oak forest turned into eucalyptus plantation, the net loss of oak forest was low and counterbalanced by its increment on former open farmland. The occurrence of a wildfire in 2003 promoted a dramatic decrease in cork oak woodlands, which mostly turned into shrubland. However, shrubland may be considered “safe sites” for ecological succession, ensuring natural cork oak regeneration and the colonization of neighboring areas.
Keywords: agroforestry systems; Eucalyptus Plantations; evergreen oak woodlands; Land Cover; Mediterranean Climate Region; Quercus suber L.